2014
DOI: 10.2147/amep.s57569
|View full text |Cite
|
Sign up to set email alerts
|

Empathy levels among health professional students: a cross-sectional study at two universities in Australia

Abstract: BackgroundEmpathy is paramount in the health care setting, optimizing communication and rapport with patients. Recent empirical evidence suggests that empathy is associated with improved clinical outcomes. Therefore, given the importance of empathy in the health care setting, gaining a better understanding of students’ attitudes and self-reported empathy is important. The objective of this study was to examine self-reported empathy levels of students enrolled in different health disciplines from two large Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
61
4
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 41 publications
11
61
4
7
Order By: Relevance
“…This is in conformity with the findings from various studies across the globe. 10,[12][13][14][15][16] Similar observation was also noted among female physicians in a study from Italy. 17 Likewise, several Indian studies have also reported higher empathy level among female medical students.…”
Section: Discussionsupporting
confidence: 69%
“…This is in conformity with the findings from various studies across the globe. 10,[12][13][14][15][16] Similar observation was also noted among female physicians in a study from Italy. 17 Likewise, several Indian studies have also reported higher empathy level among female medical students.…”
Section: Discussionsupporting
confidence: 69%
“…In a study conducted by Jabarifar et al, no significant increase or decrease was observed in the level of empathy with higher academic year in dentistry students [14]. Williams et al study showed no significant difference in the level of empathy among different year students of medical sciences including nursing, midwifery, nutrition, and pharmacy [15]. Yet, a study conducted by Shahab et al showed a significant correlation between academic year and empathy in dentistry students, and students in higher years had higher empathy scores [16].…”
Section: Discussionmentioning
confidence: 98%
“…In Australia 28 , after assessing self-reported empathy levels in students from different health careers using the same scale, it was also found that the average empathy level in women was significantly higher than the average in men and technical paramedics had the lowest reported levels.…”
Section: Discussionmentioning
confidence: 99%